A Companion to Literature and Film. - Stam, Robert (Blackwell companions in cultural studies., 2007)
A Companion to Literature and Film provides state-of-the-art research on world literature, film, and the complex theoretical relationship between them. Twenty-five essays by international experts cover the most important topics in the study of literature and film adaptations. Contributors explore, in a highly innovative and groundbreaking way, important topics in the field. These include:. * Key issues such as dialogism, hidden intertextuality, and adaptation as readings, critiques, and rewritings of source novels. * Cultural concerns including iconophobia and the word/image wars. * Theoretica.